EFFECT OF ETHEPHON SPRAYING ON SEEDS YIELD AND ITS COMPONENTS OF DIFFERENT SOYBEAN CULTIVARS - Abbas, Ahmed; Abbas, Jasim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
A field experiment was conducted at the fields of the College of Agricultural Engineering Sciences, University of Baghdad, during the summer season of 2023 to study the effects of ethephon foliar application on the growth, yield, and quality of indeterminate soybean cultivars. The experiment was carried out using a randomized complete block design (R.C.B.D) with a split-plot arrangement using three replicates. This study included three soybean cultivars (Shaimaa, Giza 22 and Giza 111) and four foliar treatments (100, 200, and 300 mg L-¹ of ethephon, along with a distilled water control). The results revealed that the Giza 22 cultivar achieved the highest means of number of pods per plant (96.16 pods plant-¹) and total seeds yield (2.51 Mg ha-1). The Shaimaa cultivar recorded the highest means of 100 seeds weight (15.88 g) and protein content (38.14%). Foliar application with concentration of 300 mg L-1 significantly enhanced the number of pods per plant (104.90 pods plant-¹), seeds per pod (2.93 seeds pod-1) and total seeds yield (2.59 Mg ha-1). Giza 22 plants treated with 300 mg L-1 exhibited the highest mean values of pods per plant (112.00 pods plant-1) and total seeds yield (3.07 Mg ha-1).